Waterproof tritium-resistant composite fabric and preparation method thereof

Through the composite technology of modified resin and membrane materials, combined with the layered structure of nanokaolin powder, an efficient tritium-retardant fabric is formed, which solves the problem of internal radiation damage of tritium and achieves good waterproof, tritium-retardant and mechanical properties.

CN119305275AActive Publication Date: 2025-01-14HUNAN INSTITUTE OF ENGINEERING
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411495498.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-14
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The β decay of tritium emits high-speed electrons, causing internal radiation damage, existing protective materials are difficult to effectively block, and traditional fabrics cannot effectively prevent tritium penetration, causing radiation damage.

Method used

Compound fabrics of modified EVA resin, modified polyvinylidene fluoride film and modified chlorinated polyethylene film are used to form an efficient barrier layer and a layer of nanokaolin powder through alcoholylation, esterification and ultraviolet grafting reaction. The structure enhances the waterproof and tritium resistance of the fabric.

Benefits of technology

Effective barriers on tritium are achieved, the waterproof and anti-aging properties of the fabric are improved, the permeability of tritium and gas penetration are reduced, and the mechanical properties of the fabric are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The invention discloses a waterproof tritium-resistant composite fabric and a preparation method thereof, and relates to the field of fabrics. When the waterproof tritium-resistant composite fabric is prepared, high-density polyethylene, 2-hydroxyethyl acrylate, allyl salicylate and chlorine react to prepare a film, and then the film is immersed in a perfluorohexanoic acid solution to obtain a modified chlorinated polyethylene film; reacting the polyvinylidene fluoride membrane with sodium p-styrenesulfonate to obtain a modified polyvinylidene fluoride membrane; the preparation method comprises the following steps: uniformly mixing nano kaolin powder, 4-pentenoyl chloride and dimethylamino ethyl acrylate to obtain modified nano kaolin powder; after alcoholysis of EVA resin, uniformly mixing the EVA resin with the modified nano kaolin powder to obtain modified EVA resin; and coating the modified EVA resin between the modified polyvinylidene fluoride film and the modified chlorinated polyethylene film, and performing hot pressing to obtain the waterproof tritium-resistant composite fabric. The waterproof tritium-resistant composite fabric prepared by the invention has excellent hydrophobic, barrier, anti-aging and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fabrics, in particular to a waterproof tritium-blocking composite fabric and a preparation method thereof. Background Art

[0002] Energy is the foundation for the maintenance and development of human civilization, but the energy resources available on the earth are limited. Traditional fossil fuels not only have limited reserves but also bring serious environmental pollution problems. Nuclear energy, as a new type of energy, has broad development prospects. There are two types of nuclear energy development: fission reactors and fusion reactors. However, since fusion reactors can release more energy, are not limited by uranium resources, and do not produce environmental pollutants such as sulfur and nitrogen oxides, nor release greenhouse gases, they are called the permanent energy of mankind in the future, and countries around the world pay close attention to them.

[0003] Tritium, the raw material of the reaction, is an isotope of hydrogen. It can produce 0.324W / g of heat through β decay. It is the main fuel for controllable thermonuclear reactors and plays an important role in the field of fusion energy. The β decay of tritium releases high-speed moving electrons, which cause internal radiation damage after entering the human body. The half-life in the human body is as long as 9 days, which can cause relatively large damage. Studies have shown that tritium can cause deterministic effect damage to the body, such as cell damage and random damage, such as carcinogenicity and genetic effects. Tritium usually exists in the form of tritium water, which has extremely strong permeability. It is easy to penetrate common protective materials and enter the human body, and cause radiation damage. Therefore, the present invention prepares a waterproof tritium barrier composite fabric with excellent barrier properties. Summary of the invention

[0004] The object of the present invention is to provide a waterproof tritium-blocking composite fabric and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A waterproof tritium-blocking composite fabric is obtained by applying a modified EVA resin between a modified polyvinylidene fluoride film and a modified chlorinated polyethylene film and then hot pressing.

[0006] As an optimization, the modified EVA resin is obtained by alcoholyzing the EVA resin and mixing it with modified nano-kaolin powder.

[0007] As an optimization, the EVA resin model is 28-150, which comes from Dongguan Maoyiyuan Plastic Raw Materials Co., Ltd.

[0008] As an optimization, the modified nano-kaolin powder is obtained by mixing nano-kaolin powder, 4-pentenoyl chloride and dimethylaminoethyl acrylate.

[0009] As an optimization, the nano kaolin powder comes from Shuangshi Mineral Products Processing Plant in Lingshou County.

[0010] As an optimization, the modified polyvinylidene fluoride membrane is obtained by reacting polyvinylidene fluoride membrane and sodium styrene sulfonate.

[0011] As an optimization, the polyvinylidene fluoride film comes from Dongguan Hualixing Plastic Raw Materials Co., Ltd.

[0012] As an optimization, the modified chlorinated polyethylene membrane is prepared by reacting high-density polyethylene, 2-hydroxyethyl acrylate, allyl salicylate and chlorine, and then immersed in a perfluorohexanoic acid solution.

[0013] As an optimization, the high-density polyethylene comes from Shanghai Qiaowei Chemical Technology Co., Ltd.

[0014] A method for preparing a waterproof tritium-blocking composite fabric comprises the following preparation steps: (1) High-density polyethylene, 2-hydroxyethyl acrylate and allyl salicylate are mixed in a mass ratio of 1:(0.1-0.2):(0.1-0.2), stirred at 50-60°C and 100-200 rpm for 25-35 min, cooled to 20-30°C, introduced chlorine for 5-15 min, heated to 130-150°C, and continued to introduce chlorine in an amount of 2-4 times the mass of high-density polyethylene, cooled to 45-55°C, introduced air, and naturally cooled to room temperature to obtain modified chlorinated polyethylene; the pre-modified chlorinated polyethylene film is immersed in a perfluorohexanoic acid solution, taken out and hung to dry until no liquid drops within 5-15 seconds, allowed to stand at 60-70°C for 6-8 hours, washed with deionized water for 3-5 times, and dried at 55-65°C for 11-13 hours to obtain a modified chlorinated polyethylene film; (2) Soak the polyvinylidene fluoride membrane in a 0.3~0.4 mol / L benzophenone methanol solution for 55~65 min, take it out, dry it at 20~30℃ for 0.5~1.5 h, move it into a quartz tube, and 2 The membrane was irradiated under ultraviolet light for 25-35 seconds, a 1%-2% sodium styrene sulfonate aqueous solution was added to cover the surface of the polyvinylidene fluoride membrane, and the irradiation was continued for 25-35 minutes. The membrane was washed with methanol and deionized water for 3-5 times, respectively, and dried at 55-65°C for 4-6 hours to obtain a modified polyvinylidene fluoride membrane. (3) Mix nano-kaolin powder, 4-pentenoyl chloride, dimethylaminoethyl acrylate, azobisisobutyronitrile and ethyl benzoate in a mass ratio of 1:(0.6-0.7):(0.7-0.9):(0.01-0.03):(3-5), ultrasonically disperse for 30-40 min, stir at 70-80 °C and 200-300 rpm for 7-9 h in a nitrogen atmosphere, cool naturally to room temperature and filter, wash with petroleum ether for 3-5 times, and dry at 85-95 °C for 11-13 h to obtain modified nano-kaolin powder; (4) EVA resin and toluene are mixed in a mass ratio of 1:(15-17), stirred at 55-65°C and 900-1000 rpm / s for 25-35 min, and a 45-55 g / L sodium hydroxide methanol solution (7-9 times the mass of the EVA resin) is added at a uniform rate within 40-50 min, and the mixture is stirred for 1-3 h. After cooling naturally to room temperature, the mixture is filtered, washed with anhydrous ethanol for 3-5 times, and dried at 45-55°C for 9-11 h to obtain an alcoholysed EVA resin; (5) Mix the alcoholyzed EVA resin and toluene in a mass ratio of 1:(8-10), perform ultrasonic dispersion for 25-35 min, add 0.02-0.04 times the mass of the alcoholyzed EVA resin modified nano-kaolin powder, stir at 900-1000 rpm / s for 25-35 min to obtain modified EVA resin; apply the modified EVA resin between the modified polyvinylidene fluoride film and the modified chlorinated polyethylene film to a thickness of 0.2-0.4 mm, dry at 70-80°C for 2-4 h, and hot press at 140-150°C and 0.5-0.7 MPa for 15-25 min to obtain a waterproof and tritium-barrier composite fabric.

[0015] As an optimization, the reaction equation of the modified chlorinated polyethylene in step (1) is: .

[0016] As an optimization, the perfluorohexanoic acid solution in step (1) is obtained by mixing perfluorohexanoic acid and methanol in a mass ratio of 1:10.

[0017] As an optimization, the pre-modified chlorinated polyethylene film in step (1) is prepared by mixing modified chlorinated polyethylene and N,N-dimethylformamide in a mass ratio of 1:4.5, stirring at 25°C and 350 rpm for 30 min, coating on a glass plate to a thickness of 2 mm, and standing at 90°C for 24 h.

[0018] As an optimization, the reaction equation of the modified chlorinated polyethylene film in step (1) is: .

[0019] As an optimization, the reaction equation of the modified polyvinylidene fluoride membrane in step (2) is: .

[0020] As an optimization, the reaction equation for alcoholysis of the EVA resin in step (4) is: .

[0021] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the waterproof tritium-blocking composite fabric, the present invention comprises the following steps: high-density polyethylene, 2-hydroxyethyl acrylate, allyl salicylate and chlorine are reacted to form a film, which is then immersed in a perfluorohexanoic acid solution to obtain a modified chlorinated polyethylene film; a polyvinylidene fluoride film is reacted with sodium styrene sulfonate to obtain a modified polyvinylidene fluoride film; nano-kaolin powder, 4-pentenoyl chloride and dimethylaminoethyl acrylate are mixed to obtain a modified nano-kaolin powder; an EVA resin is alcoholyzed and mixed with the modified nano-kaolin powder to obtain a modified EVA resin; and the modified EVA resin is applied between the modified polyvinylidene fluoride film and the modified chlorinated polyethylene film and then hot-pressed to obtain the waterproof tritium-blocking composite fabric.

[0022] First, high-density polyethylene, 2-hydroxyethyl acrylate, allyl salicylate and chlorine are reacted to form a film, which is then immersed in a perfluorohexanoic acid solution to obtain a modified chlorinated polyethylene film; a polyvinylidene fluoride film is reacted with sodium styrene sulfonate to obtain a modified polyvinylidene fluoride film; 2-hydroxyethyl acrylate and allyl salicylate are introduced into the main chain of chlorinated polyethylene through grafting modification, and allyl salicylate can absorb ultraviolet rays, remove free radicals generated by the fabric under light, heat, humidity and other environments, inhibit the oxidation reaction, and improve the anti-aging performance of the waterproof tritium barrier composite fabric; perfluorohexanoic acid is grafted by esterification reaction, and its affinity for water molecules makes it difficult for water molecules to insert into the molecular gap, thereby improving the waterproof performance of the waterproof tritium barrier composite fabric; sulfonic acid groups are introduced into the main chain of polyvinylidene fluoride through ultraviolet grafting, and the interaction with gas or liquid is increased, resulting in a decrease in the permeability of gas and liquid, thereby improving the barrier property of the waterproof tritium barrier composite fabric.

[0023] Secondly, nano-kaolin powder, 4-pentenoyl chloride and dimethylaminoethyl acrylate are mixed to obtain modified nano-kaolin powder; EVA resin is alcoholyzed and mixed with modified nano-kaolin powder to obtain modified EVA resin; the modified EVA resin is applied between a modified polyvinylidene fluoride film and a modified chlorinated polyethylene film and then hot-pressed to obtain a waterproof tritium-barrier composite fabric; 4-pentenoyl chloride and dimethylaminoethyl acrylate are polymerized on the surface of nano-kaolin powder to improve dispersibility, and the layered structure of kaolin can reduce the penetration of water and gas, thereby improving waterproofness. The barrier properties of tritium-barrier composite fabrics; the active hydroxyl groups produced by the alcoholysis of 4-pentenoyl chloride and EVA resin are used to react to form crosslinks, thereby improving the mechanical properties of the waterproof tritium-barrier composite fabrics; the amino groups on dimethylaminoethyl acrylate can react with the chlorine atoms on chlorinated polyethylene to form a positively charged quaternary ammonium structure, thereby strengthening the bonding effect between the modified chlorinated polyethylene film and the EVA resin. At the same time, it can also electrostatically bond with the sulfonic acid groups on the modified polyvinylidene fluoride film, thereby further enriching the crosslinking network and improving the mechanical properties of the waterproof tritium-barrier composite fabrics. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Embodiment 1: A method for preparing a waterproof tritium-blocking composite fabric, the method for preparing the waterproof tritium-blocking composite fabric comprising the following preparation steps: (1) High-density polyethylene, 2-hydroxyethyl acrylate and allyl salicylate were mixed in a mass ratio of 1:0.1:0.1, stirred at 50°C and 100 rpm for 35 min, cooled to 20°C, introduced chlorine for 5 min, heated to 130°C and continued to introduce chlorine twice the mass of high-density polyethylene, cooled to 45°C, introduced air, and naturally cooled to room temperature to obtain modified chlorinated polyethylene; the pre-modified chlorinated polyethylene film was immersed in a perfluorohexanoic acid solution, taken out and hung to dry until no liquid dripped within 5 seconds, allowed to stand at 60°C for 8 h, washed with deionized water 3 times, and dried at 55°C for 13 h to obtain a modified chlorinated polyethylene film; (2) The polyvinylidene fluoride membrane was soaked in 0.3 mol / L benzophenone methanol solution for 55 min, then taken out and dried at 20 °C for 1.5 h. It was then transferred into a quartz tube and heated at 7.3 mW / cm 2 The membrane was irradiated under ultraviolet light for 35 seconds, a 1% sodium styrene sulfonate aqueous solution was added to cover the surface of the polyvinylidene fluoride membrane, and the irradiation was continued for 35 minutes. The membrane was washed with methanol and deionized water for three times, respectively, and dried at 55°C for 6 hours to obtain a modified polyvinylidene fluoride membrane. (3) Nano-kaolin powder, 4-pentenoyl chloride, dimethylaminoethyl acrylate, azobisisobutyronitrile and ethyl benzoate were mixed in a mass ratio of 1:0.6:0.7:0.01:3, ultrasonically dispersed for 30 min, stirred for 9 h at 70 °C and 200 rpm in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with petroleum ether three times, and dried at 85 °C for 13 h to obtain modified nano-kaolin powder; (4) EVA resin and toluene were mixed in a mass ratio of 1:15, stirred at 55°C and 900 rpm / s for 35 min, and a 45 g / L sodium hydroxide methanol solution (7 times the mass of the EVA resin) was added at a uniform rate within 40 min. The mixture was stirred for 3 h, cooled naturally to room temperature, filtered, washed with anhydrous ethanol for 3 times, and dried at 45°C for 11 h to obtain an alcoholysed EVA resin. (5) Mix the alcoholyzed EVA resin and toluene in a mass ratio of 1:8, ultrasonically disperse for 25 minutes, add modified nano-kaolin powder in an amount of 0.02 times the mass of the alcoholyzed EVA resin, and stir at 900 rpm / s for 35 minutes to obtain modified EVA resin; apply the modified EVA resin between the modified polyvinylidene fluoride film and the modified chlorinated polyethylene film to a thickness of 0.2 mm, dry at 70°C for 4 hours, and hot press at 140°C and 0.5 MPa for 25 minutes to obtain a waterproof and tritium-barrier composite fabric.

[0026] Embodiment 2: A method for preparing a waterproof tritium-blocking composite fabric, the method for preparing the waterproof tritium-blocking composite fabric comprising the following preparation steps: (1) High-density polyethylene, 2-hydroxyethyl acrylate and allyl salicylate were mixed in a mass ratio of 1:0.15:0.15, stirred at 55°C and 150 rpm for 30 min, cooled to 250°C, introduced chlorine for 10 min, heated to 140°C and continued to introduce chlorine in an amount three times the mass of high-density polyethylene, cooled to 50°C, introduced air, and naturally cooled to room temperature to obtain modified chlorinated polyethylene; the pre-modified chlorinated polyethylene film was immersed in a perfluorohexanoic acid solution, taken out and hung to dry until no liquid dripped within 10 s, allowed to stand at 65°C for 7 h, washed with deionized water 4 times, and dried at 60°C for 12 h to obtain a modified chlorinated polyethylene film; (2) The polyvinylidene fluoride membrane was soaked in 0.35 mol / L benzophenone methanol solution for 60 min, then taken out and dried at 25 °C for 1 h. Then, it was transferred into a quartz tube and heated at 7.4 mW / cm 2 The membrane was irradiated under ultraviolet light for 30 seconds, a 1.5% sodium styrene sulfonate aqueous solution was added to cover the surface of the polyvinylidene fluoride membrane, and the irradiation was continued for 30 minutes. The membrane was washed with methanol and deionized water for 4 times, respectively, and dried at 60°C for 5 hours to obtain a modified polyvinylidene fluoride membrane. (3) Nano-kaolin powder, 4-pentenoyl chloride, dimethylaminoethyl acrylate, azobisisobutyronitrile and ethyl benzoate were mixed in a mass ratio of 1:0.65:0.8:0.02:4, ultrasonically dispersed for 35 min, stirred for 8 h at 75 °C and 250 rpm in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with petroleum ether for 4 times, and dried at 90 °C for 12 h to obtain modified nano-kaolin powder; (4) EVA resin and toluene were mixed in a mass ratio of 1:16, stirred at 60°C and 950 rpm / s for 30 min, and a 50 g / L sodium hydroxide methanol solution (8 times the mass of the EVA resin) was added at a uniform rate within 45 min. The mixture was stirred for 2 h, cooled naturally to room temperature, filtered, washed with anhydrous ethanol 4 times, and dried at 50°C for 10 h to obtain an alcoholysed EVA resin. (5) Mix the alcoholyzed EVA resin and toluene in a mass ratio of 1:9, ultrasonically disperse for 30 minutes, add modified nano-kaolin powder in an amount of 0.03 times the mass of the alcoholyzed EVA resin, and stir at 950 rpm / s for 30 minutes to obtain modified EVA resin; apply the modified EVA resin between the modified polyvinylidene fluoride film and the modified chlorinated polyethylene film to a thickness of 0.3 mm, dry at 75°C for 3 hours, and hot press at 145°C and 0.6 MPa for 20 minutes to obtain a waterproof and tritium-barrier composite fabric.

[0027] Embodiment 3: A method for preparing a waterproof tritium-blocking composite fabric, the method for preparing the waterproof tritium-blocking composite fabric comprising the following preparation steps: (1) High-density polyethylene, 2-hydroxyethyl acrylate and allyl salicylate were mixed in a mass ratio of 1:0.2:0.2, stirred at 60°C and 200 rpm for 25 min, cooled to 30°C, introduced chlorine for 15 min, heated to 150°C and continued to introduce chlorine in an amount of 4 times the mass of high-density polyethylene, cooled to 55°C and introduced air, and naturally cooled to room temperature to obtain modified chlorinated polyethylene; the pre-modified chlorinated polyethylene film was immersed in a perfluorohexanoic acid solution, taken out and hung to dry until no liquid dripped within 15 seconds, allowed to stand at 70°C for 6 hours, washed with deionized water 5 times, and dried at 65°C for 11 hours to obtain a modified chlorinated polyethylene film; (2) The polyvinylidene fluoride membrane was soaked in 0.4 mol / L benzophenone methanol solution for 65 min, then taken out and dried at 30 °C for 0.5 h. It was then transferred into a quartz tube and heated at 7.5 mW / cm 2 The membrane was irradiated under ultraviolet light for 25 seconds, a 2% sodium styrene sulfonate aqueous solution was added to cover the surface of the polyvinylidene fluoride membrane, and the irradiation was continued for 25 minutes. The membrane was washed with methanol and deionized water for 5 times, respectively, and dried at 65°C for 4 hours to obtain a modified polyvinylidene fluoride membrane. (3) Nano-kaolin powder, 4-pentenoyl chloride, dimethylaminoethyl acrylate, azobisisobutyronitrile and ethyl benzoate were mixed in a mass ratio of 1:0.7:0.9:0.03:5, ultrasonically dispersed for 40 min, stirred for 7 h at 80 °C and 300 rpm in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with petroleum ether for 5 times, and dried at 95 °C for 11 h to obtain modified nano-kaolin powder; (4) EVA resin and toluene were mixed in a mass ratio of 1:17, stirred at 65°C and 1000 rpm / s for 25 min, and a 55 g / L sodium hydroxide methanol solution (9 times the mass of the EVA resin) was added at a uniform rate within 50 min. The mixture was stirred for 1 h, cooled naturally to room temperature, filtered, washed with anhydrous ethanol for 5 times, and dried at 55°C for 9 h to obtain alcoholysed EVA resin; (5) Mix the alcoholyzed EVA resin and toluene in a mass ratio of 1:10, ultrasonically disperse for 35 minutes, add modified nano-kaolin powder in an amount of 0.04 times the mass of the alcoholyzed EVA resin, and stir at 1000 rpm / s for 25 minutes to obtain modified EVA resin; apply the modified EVA resin between the modified polyvinylidene fluoride film and the modified chlorinated polyethylene film to a thickness of 0.4 mm, dry at 80°C for 2 hours, and hot press at 150°C and 0.7 MPa for 15 minutes to obtain a waterproof and tritium-barrier composite fabric.

[0028] Comparative Example 1: A method for preparing a waterproof tritium-blocking composite fabric, the method for preparing the waterproof tritium-blocking composite fabric comprising the following preparation steps: (1) High-density polyethylene, 2-hydroxyethyl acrylate and allyl salicylate were mixed in a mass ratio of 1:0.15:0.15, stirred at 55°C and 150 rpm for 30 min, cooled to 250°C, introduced chlorine for 10 min, heated to 140°C and continued to introduce chlorine in an amount three times the mass of high-density polyethylene, cooled to 50°C and introduced air, and naturally cooled to room temperature to obtain modified chlorinated polyethylene; modified chlorinated polyethylene and N,N-dimethylformamide were mixed in a mass ratio of 1:4.5, stirred at 25°C and 350 rpm for 30 min, coated on a glass plate to a thickness of 2 mm, and allowed to stand at 90°C for 24 h to obtain a pre-modified chlorinated polyethylene film; (2) The polyvinylidene fluoride membrane was soaked in 0.35 mol / L benzophenone methanol solution for 60 min, then taken out and dried at 25 °C for 1 h. Then, it was transferred into a quartz tube and heated at 7.4 mW / cm 2 The membrane was irradiated under ultraviolet light for 30 seconds, a 1.5% sodium styrene sulfonate aqueous solution was added to cover the surface of the polyvinylidene fluoride membrane, and the irradiation was continued for 30 minutes. The membrane was washed with methanol and deionized water for 4 times, respectively, and dried at 60°C for 5 hours to obtain a modified polyvinylidene fluoride membrane. (3) Nano-kaolin powder, 4-pentenoyl chloride, dimethylaminoethyl acrylate, azobisisobutyronitrile and ethyl benzoate were mixed in a mass ratio of 1:0.65:0.8:0.02:4, ultrasonically dispersed for 35 min, stirred for 8 h at 75 °C and 250 rpm in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with petroleum ether for 4 times, and dried at 90 °C for 12 h to obtain modified nano-kaolin powder; (4) EVA resin and toluene were mixed in a mass ratio of 1:16, stirred at 60°C and 950 rpm / s for 30 min, and a 50 g / L sodium hydroxide methanol solution (8 times the mass of the EVA resin) was added at a uniform rate within 45 min. The mixture was stirred for 2 h, cooled naturally to room temperature, filtered, washed with anhydrous ethanol 4 times, and dried at 50°C for 10 h to obtain an alcoholysed EVA resin. (5) Mix the alcoholyzed EVA resin and toluene in a mass ratio of 1:9, ultrasonically disperse for 30 minutes, add modified nano-kaolin powder in an amount of 0.03 times the mass of the alcoholyzed EVA resin, and stir at 950 rpm / s for 30 minutes to obtain modified EVA resin; apply the modified EVA resin between the modified polyvinylidene fluoride film and the modified chlorinated polyethylene film to a thickness of 0.3 mm, dry at 75°C for 3 hours, and hot press at 145°C and 0.6 MPa for 20 minutes to obtain a waterproof and tritium-barrier composite fabric.

[0029] Comparative Example 2: A method for preparing a waterproof tritium-blocking composite fabric, the method for preparing the waterproof tritium-blocking composite fabric comprising the following preparation steps: (1) High-density polyethylene and 2-hydroxyethyl acrylate were mixed in a mass ratio of 1:0.15, stirred at 55°C and 150 rpm for 30 min, cooled to 250°C, chlorine gas was introduced for 10 min, the temperature was raised to 140°C, chlorine gas in an amount of 3 times the mass of high-density polyethylene was continued to be introduced, the temperature was lowered to 50°C, air was introduced, and naturally cooled to room temperature to obtain modified chlorinated polyethylene; the pre-modified chlorinated polyethylene film was immersed in a perfluorohexanoic acid solution, taken out and hung to dry until no liquid dripped within 10 s, allowed to stand at 65°C for 7 h, washed with deionized water 4 times, and dried at 60°C for 12 h to obtain a modified chlorinated polyethylene film; (2) The polyvinylidene fluoride membrane was soaked in 0.35 mol / L benzophenone methanol solution for 60 min, then taken out and dried at 25 °C for 1 h. Then, it was transferred into a quartz tube and heated at 7.4 mW / cm 2 The membrane was irradiated under ultraviolet light for 30 seconds, a 1.5% sodium styrene sulfonate aqueous solution was added to cover the surface of the polyvinylidene fluoride membrane, and the irradiation was continued for 30 minutes. The membrane was washed with methanol and deionized water for 4 times, respectively, and dried at 60°C for 5 hours to obtain a modified polyvinylidene fluoride membrane. (3) Nano-kaolin powder, 4-pentenoyl chloride, dimethylaminoethyl acrylate, azobisisobutyronitrile and ethyl benzoate were mixed in a mass ratio of 1:0.65:0.8:0.02:4, ultrasonically dispersed for 35 min, stirred for 8 h at 75 °C and 250 rpm in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with petroleum ether for 4 times, and dried at 90 °C for 12 h to obtain modified nano-kaolin powder; (4) EVA resin and toluene were mixed in a mass ratio of 1:16, stirred at 60°C and 950 rpm / s for 30 min, and a 50 g / L sodium hydroxide methanol solution (8 times the mass of the EVA resin) was added at a uniform rate within 45 min. The mixture was stirred for 2 h, cooled naturally to room temperature, filtered, washed with anhydrous ethanol 4 times, and dried at 50°C for 10 h to obtain an alcoholysed EVA resin. (5) Mix the alcoholyzed EVA resin and toluene in a mass ratio of 1:9, ultrasonically disperse for 30 minutes, add modified nano-kaolin powder in an amount of 0.03 times the mass of the alcoholyzed EVA resin, and stir at 950 rpm / s for 30 minutes to obtain modified EVA resin; apply the modified EVA resin between the modified polyvinylidene fluoride film and the modified chlorinated polyethylene film to a thickness of 0.3 mm, dry at 75°C for 3 hours, and hot press at 145°C and 0.6 MPa for 20 minutes to obtain a waterproof and tritium-barrier composite fabric.

[0030] Comparative Example 3: A method for preparing a waterproof tritium-blocking composite fabric, the method for preparing the waterproof tritium-blocking composite fabric comprising the following preparation steps: (1) High-density polyethylene, 2-hydroxyethyl acrylate and allyl salicylate were mixed in a mass ratio of 1:0.15:0.15, stirred at 55°C and 150 rpm for 30 min, cooled to 250°C, introduced chlorine for 10 min, heated to 140°C and continued to introduce chlorine in an amount three times the mass of high-density polyethylene, cooled to 50°C, introduced air, and naturally cooled to room temperature to obtain modified chlorinated polyethylene; the pre-modified chlorinated polyethylene film was immersed in a perfluorohexanoic acid solution, taken out and hung to dry until no liquid dripped within 10 s, allowed to stand at 65°C for 7 h, washed with deionized water 4 times, and dried at 60°C for 12 h to obtain a modified chlorinated polyethylene film; (2) Nano-kaolin powder, 4-pentenoyl chloride, dimethylaminoethyl acrylate, azobisisobutyronitrile and ethyl benzoate were mixed in a mass ratio of 1:0.65:0.8:0.02:4, ultrasonically dispersed for 35 min, stirred for 8 h at 75 °C and 250 rpm in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with petroleum ether for 4 times, and dried at 90 °C for 12 h to obtain modified nano-kaolin powder; (3) EVA resin and toluene were mixed in a mass ratio of 1:16, stirred at 60°C and 950 rpm / s for 30 min, and a 50 g / L sodium hydroxide methanol solution (8 times the mass of the EVA resin) was added at a uniform rate within 45 min. The mixture was stirred for 2 h, cooled naturally to room temperature, filtered, washed with anhydrous ethanol for 4 times, and dried at 50°C for 10 h to obtain an alcoholysed EVA resin. (4) Mix the alcoholyzed EVA resin and toluene in a mass ratio of 1:9, ultrasonically disperse for 30 minutes, add modified nano-kaolin powder in an amount of 0.03 times the mass of the alcoholyzed EVA resin, and stir at 950 rpm / s for 30 minutes to obtain modified EVA resin; apply the modified EVA resin between the polyvinylidene fluoride film and the modified chlorinated polyethylene film to a thickness of 0.3 mm, dry at 75°C for 3 hours, and hot press at 145°C and 0.6 MPa for 20 minutes to obtain a waterproof and tritium-barrier composite fabric.

[0031] Comparative Example 4: A method for preparing a waterproof tritium-blocking composite fabric, the method for preparing the waterproof tritium-blocking composite fabric comprising the following preparation steps: (1) High-density polyethylene, 2-hydroxyethyl acrylate and allyl salicylate were mixed in a mass ratio of 1:0.15:0.15, stirred at 55°C and 150 rpm for 30 min, cooled to 250°C, introduced chlorine for 10 min, heated to 140°C and continued to introduce chlorine in an amount three times the mass of high-density polyethylene, cooled to 50°C, introduced air, and naturally cooled to room temperature to obtain modified chlorinated polyethylene; the pre-modified chlorinated polyethylene film was immersed in a perfluorohexanoic acid solution, taken out and hung to dry until no liquid dripped within 10 s, allowed to stand at 65°C for 7 h, washed with deionized water 4 times, and dried at 60°C for 12 h to obtain a modified chlorinated polyethylene film; (2) The polyvinylidene fluoride membrane was soaked in 0.35 mol / L benzophenone methanol solution for 60 min, then taken out and dried at 25 °C for 1 h. Then, it was transferred into a quartz tube and heated at 7.4 mW / cm 2 The membrane was irradiated under ultraviolet light for 30 seconds, a 1.5% sodium styrene sulfonate aqueous solution was added to cover the surface of the polyvinylidene fluoride membrane, and the irradiation was continued for 30 minutes. The membrane was washed with methanol and deionized water for 4 times, respectively, and dried at 60°C for 5 hours to obtain a modified polyvinylidene fluoride membrane. (3) EVA resin and toluene were mixed in a mass ratio of 1:16, stirred at 60°C and 950 rpm / s for 30 min, and a 50 g / L sodium hydroxide methanol solution (8 times the mass of the EVA resin) was added at a uniform rate within 45 min. The mixture was stirred for 2 h, cooled naturally to room temperature, filtered, washed with anhydrous ethanol for 4 times, and dried at 50°C for 10 h to obtain an alcoholysed EVA resin. (4) Mix the alcoholyzed EVA resin and toluene in a mass ratio of 1:9, and ultrasonically disperse for 30 minutes to obtain a modified EVA resin; apply the modified EVA resin between the modified polyvinylidene fluoride film and the modified chlorinated polyethylene film to a thickness of 0.3 mm, dry at 75°C for 3 hours, and hot press at 145°C and 0.6 MPa for 20 minutes to obtain a waterproof and tritium-barrier composite fabric.

[0032] Test Case 1. Hydrophobicity Test method: The waterproof tritium-blocking composite fabrics obtained in each embodiment and the comparative example were taken to have the same size, and the contact angle of the surface of the modified chlorinated polyethylene film layer was measured using a contact angle meter (JC2000D1, Shanghai Zhongchen Digital Technology Equipment Co., Ltd.).

[0033] 2. Tritium barrier Test method: The waterproof tritium-blocking composite fabrics obtained in each embodiment and the comparative example were cut into square samples of 5 cm × 5 cm in size and were analyzed by 2750TR / LL low-background liquid scintillation analyzer at 25°C, 1 atm, and an initial tritium concentration of 7.48 × 108 Under the condition of Bq / L, the tritium permeation flux q was tested after 100h, and the permeability λ=q / permeation time was calculated.

[0034] 3. Mechanical properties and anti-aging properties Test method: Take samples of 80mm×30mm in size from the waterproof tritium-blocking composite fabrics obtained in each embodiment and the comparative example, and measure the breaking strength σ according to the tongue-shaped tearing method of GBT3917 using a YG(B)026HC-500 fabric strength tester at 20°C, relative humidity 65%, clamping distance 100mm, and speed 100mm / min. 0 According to GB / T16422 "Plastic Laboratory Light Source Exposure Test Method Part 3: Fluorescent UV Lamp" standard, after 7 days of ultraviolet artificial accelerated aging using the FR-1205-QUV ultraviolet aging tester of Shanghai Farui Instrument Technology Co., Ltd., the breaking strength σ was tested again 1 , calculate the strong retention rate = σ 1 / σ 0 *100%.

[0035] Table 1 below shows the analysis results of the hydrophobicity, barrier, anti-aging and mechanical properties of the waterproof tritium-barrier composite fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0036]

[0037] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the waterproof tritium-barrier composite fabric prepared by the present invention has good hydrophobic, barrier, anti-aging and mechanical properties.

[0038] By comparison, the water contact angles of Examples 1, 2, and 3 are larger than that of Comparative Example 1, indicating that the affinity of perfluorohexanoic acid grafted by esterification reaction for water molecules makes it difficult for water molecules to insert into the molecular gaps, thereby improving the waterproof performance of the waterproof tritium-blocking composite fabric.

[0039] By comparison, the strength retention rates of Examples 1, 2, and 3 are higher than those of Comparative Example 2, indicating that 2-hydroxyethyl acrylate and allyl salicylate are introduced into the main chain of chlorinated polyethylene through grafting modification. Allyl salicylate can absorb ultraviolet rays, remove free radicals generated by the fabric under light, heat, humidity and other environments, inhibit the oxidation reaction, and improve the anti-aging performance of the waterproof and tritium-barrier composite fabric.

[0040] By comparison, the permeation rates of Examples 1, 2, and 3 are lower than those of Comparative Example 3, indicating that the introduction of sulfonic acid groups on the main chain of polyvinylidene fluoride by UV grafting increases the interaction with gas or liquid, resulting in reduced permeability of gas and liquid, thereby improving the barrier properties of the waterproof tritium barrier composite fabric.

[0041] By comparison, compared with Example 4, Examples 1, 2, and 3 have lower permeation rates and greater breaking strength, which indicates that by polymerizing 4-pentenoyl chloride and dimethylaminoethyl acrylate on the surface of nano-kaolin powder to improve dispersibility, the layered structure of kaolin can reduce the permeation of water and gas and improve the barrier properties of the waterproof tritium-barrier composite fabric; the active hydroxyl groups produced by the alcoholysis of 4-pentenoyl chloride and EVA resin are reacted to form crosslinks to improve the mechanical properties of the waterproof tritium-barrier composite fabric; the amino groups on the dimethylaminoethyl acrylate can react with the chlorine atoms on the chlorinated polyethylene to form a positively charged quaternary ammonium structure, thereby strengthening the bonding effect between the modified chlorinated polyethylene film and the EVA resin, and at the same time, can also electrostatically bond with the sulfonic acid groups on the modified polyvinylidene fluoride film to further enrich the crosslinking network and improve the mechanical properties of the waterproof tritium-barrier composite fabric.

[0042] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A waterproof tritium-blocking composite fabric, characterized in that: The waterproof tritium-blocking composite fabric is obtained by applying modified EVA resin between a modified polyvinylidene fluoride film and a modified chlorinated polyethylene film and then hot pressing; The modified EVA resin is obtained by mixing the alcoholysis of EVA resin with modified nano-kaolin powder; The modified nano-kaolin powder is obtained by mixing nano-kaolin powder, 4-pentenoyl chloride and dimethylaminoethyl acrylate; The modified polyvinylidene fluoride membrane is obtained by reacting a polyvinylidene fluoride membrane with sodium styrene sulfonate; The modified chlorinated polyethylene film is prepared by reacting high-density polyethylene, 2-hydroxyethyl acrylate, allyl salicylate and chlorine, and then immersed in a perfluorohexanoic acid solution.

2. A method for preparing a waterproof tritium-blocking composite fabric, characterized in that: The method comprises the following preparation steps: (1) High-density polyethylene, 2-hydroxyethyl acrylate and allyl salicylate are mixed in a mass ratio of 1:(0.1-0.2):(0.1-0.2), stirred at 50-60°C and 100-200 rpm for 25-35 min, cooled to 20-30°C, and chlorine gas is introduced for 5-15 min, heated to 130-150°C, and chlorine gas of 2-4 times the mass of high-density polyethylene is continuously introduced, cooled to 45-55°C, and air is introduced, and naturally cooled to room temperature to obtain modified chlorinated polyethylene; the pre-modified chlorinated polyethylene film is immersed in a perfluorohexanoic acid solution, taken out and hung to dry until no liquid drops within 5-15 seconds, allowed to stand at 60-70°C for 6-8 hours, washed with deionized water for 3-5 times, and dried at 55-65°C for 11-13 hours to obtain a modified chlorinated polyethylene film; (2) Soak the polyvinylidene fluoride membrane in a 0.3~0.4 mol / L benzophenone methanol solution for 55~65 min, take it out, dry it at 20~30℃ for 0.5~1.5 h, move it into a quartz tube, and 2 The membrane was irradiated under ultraviolet light for 25-35 seconds, a 1%-2% sodium styrene sulfonate aqueous solution was added to cover the surface of the polyvinylidene fluoride membrane, and the irradiation was continued for 25-35 minutes. The membrane was washed with methanol and deionized water for 3-5 times, respectively, and dried at 55-65°C for 4-6 hours to obtain a modified polyvinylidene fluoride membrane. (3) Mix nano-kaolin powder, 4-pentenoyl chloride, dimethylaminoethyl acrylate, azobisisobutyronitrile and ethyl benzoate in a mass ratio of 1:(0.6-0.7):(0.7-0.9):(0.01-0.03):(3-5), ultrasonically disperse for 30-40 min, stir at 70-80 °C and 200-300 rpm for 7-9 h in a nitrogen atmosphere, cool naturally to room temperature and filter, wash with petroleum ether for 3-5 times, and dry at 85-95 °C for 11-13 h to obtain modified nano-kaolin powder; (4) EVA resin and toluene are mixed in a mass ratio of 1:(15-17), stirred at 55-65°C and 900-1000 rpm / s for 25-35 min, and a 45-55 g / L sodium hydroxide methanol solution (7-9 times the mass of the EVA resin) is added at a uniform rate within 40-50 min, and the mixture is stirred for 1-3 h. After cooling naturally to room temperature, the mixture is filtered, washed with anhydrous ethanol for 3-5 times, and dried at 45-55°C for 9-11 h to obtain an alcoholysed EVA resin; (5) Mix the alcoholyzed EVA resin and toluene in a mass ratio of 1:(8-10), perform ultrasonic dispersion for 25-35 min, add 0.02-0.04 times the mass of the alcoholyzed EVA resin modified nano-kaolin powder, stir at 900-1000 rpm / s for 25-35 min, and obtain a modified EVA resin; The modified EVA resin is applied between the modified polyvinylidene fluoride film and the modified chlorinated polyethylene film to a thickness of 0.2-0.4 mm, dried at 70-80° C. for 2-4 hours, and hot-pressed at 140-150° C. and 0.5-0.7 MPa for 15-25 minutes to obtain a waterproof tritium-blocking composite fabric.

3. The method for preparing a waterproof tritium-blocking composite fabric according to claim 2, characterized in that: The reaction equation of the modified chlorinated polyethylene in step (1) is: 。 4. The method for preparing a waterproof tritium-blocking composite fabric according to claim 2, characterized in that: The perfluorohexanoic acid solution in step (1) is obtained by mixing perfluorohexanoic acid and methanol in a mass ratio of 1:

10.

5. The method for preparing a waterproof tritium-blocking composite fabric according to claim 2, characterized in that: The pre-modified chlorinated polyethylene film in step (1) is prepared by mixing modified chlorinated polyethylene and N,N-dimethylformamide in a mass ratio of 1:4.5, stirring at 25°C and 350 rpm for 30 minutes, coating on a glass plate to a thickness of 2 mm, and standing at 90°C for 24 hours.

6. The method for preparing a waterproof tritium-blocking composite fabric according to claim 2, characterized in that: The reaction equation of the modified chlorinated polyethylene film in step (1) is: 。 7. The method for preparing a waterproof tritium-blocking composite fabric according to claim 2, characterized in that: The reaction equation for the modified polyvinylidene fluoride membrane in step (2) is: 。 8. The method for preparing a waterproof tritium-blocking composite fabric according to claim 2, characterized in that: The reaction equation for the alcoholysis of the EVA resin in step (4) is: 。

Citation Information

Patent Citations

  • Tritium-proof wear-resistant reinforced polymer composite material and preparation method thereof

    CN115489184A

  • Tritium-proof polymer composite material for window and preparation method of tritium-proof polymer composite material

    CN116476487A

  • Modified burn characteristic Saranex film

    US5250350A

  • dispersant

    WO2000017250A1